Hubungan antara Pengelolaan Lingkungan Belajar dengan Perkembangan Sosial Anak Usia Dini Menurut Wali Murid di PAUD Falamboyan Parit Malintang Kabupaten Padang Pariaman - Suci Ramadani; Ismaniar Ismaniar; Vevi Sunarti (Universitas Negeri Padang, 2018)
This research is motivated by the problem of many early childhood problematic at the stage of social development in PAUD Falamboyan Parit Malintang Padang Pariaman District. This is presumably because the management of the learning environment has not been well implemented, so this study aims to reveal the description of the management of the learning environment, the picture of early child social development, and the relationship between the two variables. This research is correlational research. The research population is the guardian of murid di jadikan sampel by using stratified random sampling technique. Data collection tool used is a questionnaire with data analysis of percentage calculations and using product moment formula to see the relationship of these two variables. The results showed that the Relationship Management Environmental Learning With Social Development Early Childhood According to the Guardian in Paud Falamboyan Parit Malintang Padang Pariaman District looks less good.